(untitled) (Universal International Scientific Journal, 2026)
This paper explores the stages of formation of symbol and allegory in Eastern poetics and examines their aesthetic and poetic functions. Drawing on examples from ancient Indian, Persian Turkic, and Islamic literary traditions, the study analyzes the development of symbol and allegory as artistic devices conveying moral, philosophical, religious, and social meanings. Special attention is given to the role of symbolism in Jadid literature and in Uzbek literature of the independence period as a means of social criticism, national consciousness, and philosophical reflection